2017
DOI: 10.24200/sci.2017.4268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of edge rate of the designed line markings on the following time headway

Abstract: Abstract. Time headway is an important indicator for evaluating car-following safety.To study the in uence of edge rate on time headway in car-following, three patterns of line marking were designed and placed on a real-world expressway, with actual vehicle ow data collected. Statistical analyses showed that (1) Time headways raised after the installation of line markings compared with the original situation; and (2) When the value of edge rate fell in [5 Hz,14 Hz], the time headway rose along the increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Actually, the influence of visual perception on driving behaviors and collision avoidance was originally noticed by some cognitive psychologists, who verified in virtual-reality scenes that the existence of certain visual information (which was termed as "visual cues") on ground surface could lead to drivers' overestimation of speed [42,44,48,62,63], underestimation of distance [44,[64][65][66][67][68][69][70], and untimely and inadequate brake [42,43]. Inspired by those cognitive psychologists, Ding et al [14,21,24,71,72] conducted a series of studies focusing on associating, evaluating, and explaining the effects and mechanism of drivers' speed perception and distance perception on car-following behaviors and crash risk, by introducing and testing several specially designed perceptual markings with on-road experiments and observations. In addition, the inherent connection between speed/distance perception, driving behaviors, and crash risk was comprehensively accounted for by two latent variables, i.e., "speed risk perception (SRP)" and "distance risk perception (DRP)," which differentiated the risk perception originating from variations in speed and distance [14].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, the influence of visual perception on driving behaviors and collision avoidance was originally noticed by some cognitive psychologists, who verified in virtual-reality scenes that the existence of certain visual information (which was termed as "visual cues") on ground surface could lead to drivers' overestimation of speed [42,44,48,62,63], underestimation of distance [44,[64][65][66][67][68][69][70], and untimely and inadequate brake [42,43]. Inspired by those cognitive psychologists, Ding et al [14,21,24,71,72] conducted a series of studies focusing on associating, evaluating, and explaining the effects and mechanism of drivers' speed perception and distance perception on car-following behaviors and crash risk, by introducing and testing several specially designed perceptual markings with on-road experiments and observations. In addition, the inherent connection between speed/distance perception, driving behaviors, and crash risk was comprehensively accounted for by two latent variables, i.e., "speed risk perception (SRP)" and "distance risk perception (DRP)," which differentiated the risk perception originating from variations in speed and distance [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Generally, most of the experimental sites, designs, and processes of data collection and data treatment had already been demonstrated in previous studies [14,71,72], which will be briefly mentioned here. erefore, the variable selection and description are of primary focus to be explained in this study.…”
Section: Experiments and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al (2013) studied the influence of the plane layout of the edge rate lines on the speed reduction effect, and found that the double-row edge rate lines had better speed reduction effect. Furthermore, through road experiments, Ding et al (2017aDing et al ( , 2017bDing et al ( , 2019 found that edge rate marking can not only reduce the speed, but also increase the headway time, the cycle length of edge rate lines selected by the experiment were 2 m.…”
Section: Introductionmentioning
confidence: 99%